Community Forest Management in Liberia - Recommendations for CSOs - Yiah, J.W. (2020)
As part of a multi-country review of community forest rights, the Sustainable Development Institute conducted a review of community forest rights in Liberia. The review documented stakeholders’ experiences with, and views on, the Community Forest Management Agreements, with a focus on the conditions and constraints for success. In this policy brief we summarize some of the main outcomes of the review, and the consequent recommendations for CSOs.